Aedes Vector Surveillance in the Southeastern United States Reveals Growing Threat of Aedes japonicus japonicus (Diptera: Culicidae) and Aedes albopictus. Issue 6 (3rd July 2019) - McKenzie, Benjamin A; Stevens, Kelly; McKenzie, Ansley E; Bozic, Jovana; Mathias, Derrick; Zohdy, Sarah
Abstract: Mosquito-borne diseases are on the rise globally, and have the potential to thrive along the Gulf Coast of the United States, where subtropical conditions may facilitate the introduction or movement of mosquito vectors. Despite surveillance efforts, Aedes aegypti (L.) had not been detected in the Gulf state of Alabama for nearly three decades. The detection of Ae. aegypti in Alabama may suggest remnant or reemergent populations of this vector. We conducted adult sampling between May and August of 2018 to capture mosquitoes during a time frame when all species should be active. This was to ensure no species were missed due to overwintering and to identify the distributions of Aedes mosquitoes of medical importance. No Ae. aegypti were detected in Alabama over the period of this study. We detected Aedes albopictus (Skuse) in 65 counties and the recently invasive Aedes japonicus japonicus (Theobald) in 30 counties across the state. These results indicate that while Ae. aegypti was recently reported from parts of Alabama, the state is not experiencing a major resurgence of the species, whereas Ae. albopictus remains ubiquitous. Further, results indicate that a third wave of Aedes invasion may be occurring, that of Ae. japonicus japonicus . All three of these species are medically important vectors and may pose threats to the public health of the Gulf Coast of the United States.